Irrigation system performance assessment and diagnosis - Murray-Rust, Hammond; Snellen, W.B. (International Irrigation Management Institute, 1993)
Frame work for use in assessment of irrigation system performance and diagnosis of the primary causes of different levels of performance actually achieved . The framework is tested using 15 case studies of irrigation performance in a range of countries in Asia, Africa and South America with a number of different design and management environments.